Penguatan Daya Saing UMKM Produk Lokal di Wilayah Perbatasan - Ardheta, Preztika Ayu; Mustika, Maya; Santoso, Joko Bagio; Pragiwani, Meita; Sakti, Sri Handoko (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2026)
Border areas possess significant economic potential through the development of local products based on natural resources and local wisdom. Kabupaten Kepulauan Sangihe, particularly Tahuna, is a border region with substantial opportunities to strengthen MSMEs in fisheries, agriculture, and distinctive local food products. However, the utilization of this potential remains constrained by limited market access, technology adoption, and human resource capacity. This Community Service Program (PKM) aims to identify opportunities and challenges in strengthening regional economic development through local products in border areas, using a participatory online approach. The methods employed include socialization sessions, workshops, group discussions, needs assessments of MSME actors, and question-and-answer sessions, all of which serve as indicators of participants’ level of understanding. The results indicate that local products have strong growth potential through the use of digital technology and marketing networks. Nevertheless, MSMEs continue to face challenges related to product quality, business legality, digital literacy, and limited access to financing. This program is expected to serve as a foundation for formulating sustainable MSME strengthening strategies in border areas through technological optimization and improved financial support mechanisms.